Estoque de carbono nos solos da bacia do Rio Araguari-MG: estimativas, modelagem e cenários - Rosendo, Jussara dos Santos (2010)
The soils can act as a source or carbon sink to the atmosphere, depending on the climate conditions and, especially, the type of use and management adopted. Taking into consideration the stock/sequestration carbon potential, admittedly, attributed to several land uses, as in planted forests (Pinus and Eucaliptus), and no-till areas, as well as the efficiency in stocking C in the soils under pastures, is the objective of this research: the reforestation (REF), the annual irrigated cultivation (CAI); the direct plantation (PDI); the coffee (CAF), sugarcane (CAN), improved pasture (PME) and degraded pasture (PDE), in comparison to cerrado s natural vegetation, more specifically the vegetation type named Cerrado/Cerradão (CER), that s the typical vegetation, which is inserted to Araguari s river (MG state), to the depth of 0-20 cm and 20-40 cm. The river basin of Araguari River, located in the mesoregion of Triângulo and Alto Paranaíba, west portion of Minas Gerais State it s located among the geographic coordinates 18º 20 and 20º 10 latitude South and 46º 00 and 48º 50' longitude West from Greenwich, occupying an area of about 20.186 km², covering part of 20 municipalities. The results of the research showed that the agriculture and livestock have a high potential to stock C in the soil. The average C stock from different land uses, presented in Rio Araguari s river basin, varied from 34,63 Mg C ha-1 to 49,64 Mg C ha-1 in 0-20 cm depth, values related to the average of degraded pasture (PDE) and annual irrigated plantation (CAI), respectively. To 20-40 cm depth, the lower estimate observed also belongs to PDE, with about 27,51 Mg C ha-1, in which the highest value estimated is related to the average of C stocks present in the coffee areas (CAF). The areas of CER, that represent the reference system of this research, present values from 38,05 Mg C ha-1 to 0-20 cm depth, and 26,80 Mg C ha-1, to 20-40 cm. It was verified that Century model simulated in a satisfactory way the C stock of the uses evaluated (PME, PDE and CAN), once that, the C values measured in field were very similar to those estimated by the model. Therefore, based on the simulation, the use which presented a larger C stocking potential in the soil until the year of 2100 was the PME PME (66,99 Mg C ha-1). The land use and vegetation cover allowed the quantification of different categories of uses in Rio Araguari s river basin, distributed, to their of 1973 and 2009, as follows: Cerradão/Forest (16,89 % in 1973 and 12,70 % in 2009); Cerrado (7,26 % in 1973 and 1,67 % in 2009); Dry Grassland (52,60 % in 1973 and 19,50 % in 2009); Grassland (8,59 % in 1973 and 5,71 % in 2009); Reforestation (0,90 % in 1973 and 3,52 % in 2009); Pasture (10,55 % in 1973 and 29,73 % in 2009); Annual Plantation (2,39 % in 1973 and 19,40 % in 2009); Sugarcane (2,48 % in 2009); Annual Irrigated Plantation (1,66 % in 2009); Perennial Plantation Coffee (0,18 % in 2009); Mineral Influence (0,06 % in 2009); Urban Influence (0,53 in 1973 and 1,02 % in 2009); Water (0,30 % in 1973 and 2,35 % in 2009). From the basin s total área (in 2009), more than 60% are occupied by anthropic use, among these, 29,73% are destined to livestock, which is the predominant economic activity in the area. In 1973, the stocked carbon in the soil was from, the most part of it, natural vegetation, a sum of 34,8 Tg C (almost 50% from the total estimative of C) of over 71,0 Tg C estimated. In 2009, the opposite was verified, the most part of the stocked C happened through anthropic use (49,57 Tg C), with a bigger contribution from annual plantations under direct plantation system, almost 19 Tg C, while the stocked C through natural vegetation corresponds to 29,71 Tg C. Some change simulations of the land use were done from 2009 until 2100, highlighting the conversion of the areas under PDE to CAN, and the recovery of PDE s areas, reducing them to less of than 1% of the total basin area, the impact of these modifications totaled more than 16 Tg of C stocked in the soil.